2009
DOI: 10.1073/pnas.0907766106
|View full text |Cite
|
Sign up to set email alerts
|

Distinct and overlapping roles for two Dicer-like proteins in the RNA interference pathways of the ancient eukaryote Trypanosoma brucei

Abstract: Trypanosoma brucei is one of the most ancient eukaryotes where RNA interference (RNAi) is operational and is the only single-cell pathogen where RNAi has been extensively studied and used as a tool for functional analyses. Here, we report that the T. brucei RNAi pathway, although relying on a single Argonaute protein (AGO1), is initiated by the activities of two distinct Dicer-like enzymes. Both TbDCL1, a mostly cytoplasmic protein, and the previously undescribed nuclear enzyme TbDCL2 contribute to the biogene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
103
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(115 citation statements)
references
References 24 publications
10
103
1
Order By: Relevance
“…4). In contrast, the multidomain structure of the Dicer enzymes of higher eukaryotes is not well maintained among protists (Cerutti and CasasMollano, 2006) and an RNaseIII motif might be all that is strictly required for function (Cerutti and Casas-Mollano, 2006;Patrick et al, 2009). RDR-related proteins are structurally conserved but, consistent with an ancillary role in typical RNAi (Cerutti and CasasMollano, 2006), they appear to have a fairly limited taxonomic distribution among the examined microalgae (Table 1).…”
Section: Phylogenetic Analysis and Domain Organization Of Core Componmentioning
confidence: 99%
“…4). In contrast, the multidomain structure of the Dicer enzymes of higher eukaryotes is not well maintained among protists (Cerutti and CasasMollano, 2006) and an RNaseIII motif might be all that is strictly required for function (Cerutti and Casas-Mollano, 2006;Patrick et al, 2009). RDR-related proteins are structurally conserved but, consistent with an ancillary role in typical RNAi (Cerutti and CasasMollano, 2006), they appear to have a fairly limited taxonomic distribution among the examined microalgae (Table 1).…”
Section: Phylogenetic Analysis and Domain Organization Of Core Componmentioning
confidence: 99%
“…2A; Patrick et al 2009). If the 59 ends of tRNA introns that accumulate in xrn1D cells have a terminal phosphate, CIP treatment could lead to a change in electrophoretic mobility; in contrast, TEX treatment would result in intron degradation.…”
Section: Monophosphorylation Is Requisite Prior To Intron Degradationmentioning
confidence: 99%
“…In contrast, 5 These authors contributed equally to this work. 6 siRNAs are ubiquitous and abundant in many protozoa (Robinson and Beverley 2003;Ullu et al 2005;Zhang et al 2008;Patrick et al 2009;Lye et al 2010;Tschudi et al 2012), suggesting that siRNAs, but not miRNAs, may be the key molecules in the RNA interference (RNAi) pathway in protozoan species.…”
Section: Introductionmentioning
confidence: 99%
“…Trypanosoma brucei is one of the most ancient eukaryotes in which RNAi has been discovered and extensively studied (Patrick et al 2009). It has been reported that endo-siRNAs in T. brucei could be derived from retroposons and repeat sequences to control retroposon transcript abundance (Djikeng et al 2001).…”
Section: Introductionmentioning
confidence: 99%